2018
DOI: 10.1007/s00253-017-8724-4
|View full text |Cite
|
Sign up to set email alerts
|

Cr(VI) reduction and physiological toxicity are impacted by resource ratio in Desulfovibrio vulgaris

Abstract: Desulfovibrio spp. are capable of heavy metal reduction and are well-studied systems for understanding metal fate and transport in anaerobic environments. Desulfovibrio vulgaris Hildenborough was grown under environmentally relevant conditions (i.e., temperature, nutrient limitation) to elucidate the impacts on Cr(VI) reduction on cellular physiology. Growth at 20 °C was slower than 30 °C and the presence of 50 μM Cr(VI) caused extended lag times for all conditions, but once growth resumed the growth rate was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…shown for Desulfovibrio, the mechanism (Type I or II) under the nutrient deprived state is not 95 known. We recently demonstrated that nutrient ratios impacted metal interactions (i.e., Cr(VI) 96 sensitivity) in Desulfovibrio (Franco et al 2018), and therefore, hypothesized that nutrient 97 imbalance would impact reduction-oxidation reactions in Desulfovibrio biofilms grown on a metal 98 surface.…”
mentioning
confidence: 99%
“…shown for Desulfovibrio, the mechanism (Type I or II) under the nutrient deprived state is not 95 known. We recently demonstrated that nutrient ratios impacted metal interactions (i.e., Cr(VI) 96 sensitivity) in Desulfovibrio (Franco et al 2018), and therefore, hypothesized that nutrient 97 imbalance would impact reduction-oxidation reactions in Desulfovibrio biofilms grown on a metal 98 surface.…”
mentioning
confidence: 99%
“…The return of the upp gene restores sensitivity, providing a counterselectable gene. JW710 also allows site-directed mutations ( 13 ) and multiple deletions to be created without an accumulation of selectable markers ( 12 , 14 ). The plasmids, pSC27 ( 15 ), pMO719 ( 16 ), pMO9075 ( 11 ), and pMO746 ( 17 ), with features used in various strain constructions, are available from https://www.addgene.org/Judy_Wall/ .…”
Section: Announcementmentioning
confidence: 99%
“…), 11.5 cm (height) glass column packed with approximately 760 (6 mm diameter) glass beads and hydraulic loading rate of 40 mL/h (across a pore volume of 60 mL) to achieve a hydraulic retention time of 1.5 h. Reactors operated under optimal loading conditions towards steadystate operation were challenged by NADH inhibitors, cytochrome-b inhibitors and ATPase uncouplers at different times of operation to evaluate the electron pathway mechanisms in the organisms. Continuation of Cr(VI) reduction activity after blocking cytochrome-b activity would indicate Cr(VI) reduction via NADH-dehydrogenase [87] or Cr(VI) reduction connected to sulphate shuttle mechanisms that can also transport chromate (CrO 4 2−…”
Section: Example Of Case Study For Lab-scale and Pilot-scale Evaluationmentioning
confidence: 99%
“…) into the cytoplasm of the cell [30,87,88]. Cr(VI) reduction in the presence of uncouplers could imply membrane associated Cr(VI) reduction pathway via the membrane electron phosphorylation transport system [87].…”
Section: Example Of Case Study For Lab-scale and Pilot-scale Evaluationmentioning
confidence: 99%
See 1 more Smart Citation